EKSPLORASI DAN KARAKTERISASI KANTONG SEMAR (Nephentes sp.) DI KAMPUS UIN SUSKA RIAU - Rosmaina Rosmaina; Zulfahmi Zulfahmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
Pitcher plant (Nepenthes sp) is a member of Nepenthaceae family. In Riau Province, pitcher plant is known locally as Periuk monyet. This species is economically important due to used as ornamental and medicine plants. In the present study, we want to know the kind of pitcher plant in peat swamp forest of State Islamic University of Sultan Syarif Kasim (UIN SUSKA) Riau. The result of exploration found that there are four species of Nepenthes growth in peat swamp forest of UIN SUSKA Riau, namely: N. ampularia, N. gracillis, N. mirabilis, and one species is estimated hybrid between N. ampularia x N. gracillis (Nepenthes x trichocharpa). The number of hybrid between N. ampularia x N. gracillis is found restricted, so that it is required another study to ensure that phenomenon.